Undo the brake of tumour immune tolerance with antibodies, peptide mimetics and small molecule compounds targeting PD‐1/PD‐L1 checkpoint at different locations for acceleration of cytotoxic immunity to cancer cells. (29th January 2019) - Gu, Wenyi; Wang, Lihui; Wu, Yanheng; Liu, Jun‐Ping
Summary: Recent clinical success of immunotherapy that inhibits the negative immune regulatory pathway programmed cell death protein‐1/PD‐1 ligand 1 (PD‐1/PD‐L1) has initiated a new era in the treatment of metastatic cancer. However, greater challenges remain to treat all cancers. The molecular architecture in the immune synapse constituting positive engagements for immune activation and negative checkpoints against immune hyperactivity is regulated dynamically by interaction between proteostasis and tumour microenvironment. This article reviews recent progresses in our understandings of the cellular and molecular mechanisms of the negative checkpoint PD‐1/PD‐L1 behaviours in immune tolerance of tumourigenesis and metastasis. We provide an overview on PD‐L1 gene expression regulation, protein turnover, intra‐ and extracellular trafficking, exosome‐mediated inter‐cellular transport, molecular interface peptide mimetics, inhibitory chemical compounds such as metformin, and antibody dynamics. We summarise PD‐L1 post‐translational modifications including glycosylation, palmitoylation, phosphorylation and ubiquitination, reflecting future research directions and opportunities in identifying tumour‐specific signalling targets, their regulatory molecules and pathways for intervention into various types of cancers.